The Effects of Switching from Sevoflurane to Short-Term Desflurane prior to the End of General Anesthesia on Patient Emergence and Recovery: A Randomized Controlled Trial. (6th July 2022) - Kim, Ji Wook; Lee, Jeong Yup; Hwang, Si Won; Kang, Dong-Hee; Ryu, Sie Jeong; Kim, Doo Sik; Kim, Ju Deok
Abstract : While sevoflurane and desflurane have been regarded as inhalation agents providing rapid induction and emergence, previous studies demonstrated the superiority of desflurane-anesthesia compared to sevoflurane-anesthesia in the postoperative recovery in obese and geriatric patients. We investigated whether a short-term switch of sevoflurane to desflurane at the end of sevoflurane-anesthesia enhances patient postoperative recovery profile in non-obese patients. We randomly divide patients undergoing elective surgery (n = 60) into two groups: sevoflurane-anesthesia group (Group-S, n = 30 ) and sevoflurane-desflurane group (Group-SD, n = 30 ). In Group-S, patients received only sevoflurane-anesthesia until the end of surgery (for >2 hours). In Group-SD, sevoflurane was stopped and switched to desflurane-anesthesia before the completion of sevoflurane-anesthesia (for approximately 30 minutes). We assessed the intergroup differences in the times to get eye-opening, extubation, and a bispectral index of 80 (BIS-80). Group-SD showed significantly shorter times to get eye-opening (438 ± 101 vs. 295 ± 45 s; mean difference, 143 s; 95% confidence interval [CI], 101–183; p < 0.001 ), extubation (476 ± 108 vs. 312 ± 42 s; mean difference, 164 s; 95% CI, 116–220; p < 0.001 ), and BIS-80 (378 ± 124 vs. 265 ± 49 minutes; mean difference, 113 s; 95% CI, 58–168 p < 0.001 ) compared to Group-S. There was no between-group difference in postoperative nausea, vomiting, and hypoxia incidences. Our results suggested that the short-term (approximately 30 minutes) switch of sevoflurane to desflurane at the end of sevoflurane-anesthesia can facilitate the speed of postoperative patient recovery.